Investigation of heavy metal contamination and ecological and health risks in farmland soils from southeastern phosphate plateaus of Khouribga (Morocco) - Barakat, Ahmed; Khellouk, Rida; Ennaji, Widad; Mosaid, Hassan (Ecological Questions, 2022)
The present study was conducted in the SE area of phosphate plateaus (Khouribga) located in central Morocco. It attempted to assess the heavy metal (HM) (Cd, Cr, Cu, Pb, Zn) contamination in the farmland soils and their potential ecological hazard and non-non-carcinogenic risks using various pollution indices, magnetic susceptibility (MS), and Geographical Information System (GIS) methods. A total of 41 soil samples were collected and analyzed for pH, electrical conductivity (EC), grain-size, organic matter (OM), calcium carbonate (CaCO3), and MS and HM elements. The results showed a mean dominance order of Zn>Cr>Cu>Pb>Cd where mean concentrations of HMs, except Pb, exceeded their local background and Food and Agriculture Organization (FAO) and World Health Organization (WHO) permissible guidelines. The values of geo-accumulation index (Igeo), nemerow pollution index (PI), and pollution load index (PLI) revealed significant high level of HM contamination in soils. The MS values showed a spatial distribution pattern similar to those of HMs, attesting the ability of the MS method for mapping the contaminated soils. Agricultural and mining activities and geologic materials were the main sources of HM accumulation. According to the potential ecological risk index (RI) (195.93<RI<1092.53), the soil samples had moderate (65.85%) to high ecological (34.15%) risk. The hazard index (HI) showed that adults and children are not exposed to non-carcinogenic risk from the studied HMs, apart from two soil samples where Cd posed health risks to children compared to the other studied HMs. The statistical results revealed that soils are polluted by anthropogenic activities. Accordingly, effective agricultural practices that respect the environment, including the reduction of inputs as fertilizers, pesticides, herbicides, and fungicides should be required to guarantee the safety of cropland and the residents in the studied area. Hence, the findings from this study provided some useful information for soil pollution control and management in the study area.